2018
DOI: 10.1038/s41598-018-27810-6
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen promotes progression of hormone-dependent breast cancer through CCL2-CCR2 axis by upregulation of Twist via PI3K/AKT/NF-κB signaling

Abstract: The chemokine (C-C motif) ligand 2 (CCL2) with its cognate receptor chemokine (C-C motif) receptor 2 (CCR2) plays important roles in tumor invasion and metastasis. However, the mechanisms and mediators for autocrine CCL2 and CCL2-CCR2 axis remain elusive in breast cancer. Here we examined the levels of CCL2 in 4 breast cancer cell lines along with 57 human breast cancer specimens and found them significantly increased with presence of 17β-estradiol (E2) in estrogen receptor (ER)-positive breast cancer cells, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
53
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(60 citation statements)
references
References 50 publications
2
53
0
Order By: Relevance
“…These results correlated with recent in vitro and in vivo clinical data, where bone marrow-derived macrophage efferocytosis of cancer cells promotes the expression of CCL5, CXCL1, CXCL5, and IL-6 pro-inflammatory cytokines that accelerate tumor progression in the bone microenvironment [7]. The roles of these cytokines have been previously associated with tumor inflammation mechanisms and metastasis in various cancer types [7,[35][36][37][38]. In accordance with this hypothesis, we found that inducing bone marrow macrophage repolarization with IFN-γ towards M1-type resulted in a significant downregulation of Cxcl1, Cxcl4, and Cxcl5 expression in efferocytic macrophages, which was corroborated by the CXCL1 and CXCL5 ELISA results.…”
Section: Discussionsupporting
confidence: 87%
“…These results correlated with recent in vitro and in vivo clinical data, where bone marrow-derived macrophage efferocytosis of cancer cells promotes the expression of CCL5, CXCL1, CXCL5, and IL-6 pro-inflammatory cytokines that accelerate tumor progression in the bone microenvironment [7]. The roles of these cytokines have been previously associated with tumor inflammation mechanisms and metastasis in various cancer types [7,[35][36][37][38]. In accordance with this hypothesis, we found that inducing bone marrow macrophage repolarization with IFN-γ towards M1-type resulted in a significant downregulation of Cxcl1, Cxcl4, and Cxcl5 expression in efferocytic macrophages, which was corroborated by the CXCL1 and CXCL5 ELISA results.…”
Section: Discussionsupporting
confidence: 87%
“…In mice that have received the subcutaneous injection of LLC cancer cells, treatment with a CCR2 antagonist (RS504393) inhibits the establishment of lung metastatic foci ( 100 ). A recent study also showed that another CCR2 antagonist (RS102896) can suppress liver metastasis of MCF-7 human breast cancer cells induced by estrogen ( 101 ). Furthermore, in mice that have developed orthotopic tumors by 4T1 mammary tumor cells, treatment with a CCR5 antagonist (maraviroc) reduces metastatic tumor burden in the lung ( 95 ).…”
Section: Therapeutic Potential Of Chemokine Antagonists To Prevent Mamentioning
confidence: 99%
“…NF-κB and STAT3 have been revealed to regulate inflammation and cell adhesion [ 35 ]. In addition, Twist had the function of regulating NF-κB pathway [ 36 ]. In our study, the expression of Twist, NF-κB and STAT3 were detected to evaluate the NF-κB signaling pathway in high glucose-induced HGMCs and HRGECs.…”
Section: Discussionmentioning
confidence: 99%